NURTURING CREATIVITY THROUGH THE REGGIO EMILIA APPROACH: A STUDY OF EARLY LEARNING PRACTICES IN MALAYSIAN TASKA - TUAN ELISYA MAISARAH TUAN SOUPI; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
Fostering Creativity via the Reggio Emilia Approach: An Examination of Early Learning Practices in Malaysian TASKA. This article examines the application of the Reggio Emilia Approach in Malaysian Taman Asuhan Kanak-Kanak (TASKA) and its significance in fostering creativity and comprehensive development in young children. The Reggio Emilia philosophy, originating in Italy, perceives children as competent, curious, and capable learners who articulate themselves through many kinds of communication, commonly termed the